Parenting mediation practices on the use of gadgets among preschool children in selected urban setting in the Philippines - Faraon, Arlene Robina N.; Jamero, Josephine Louise; Roldan, Aurorita (Quezon City University of the Philippines Diliman, 2024)
This study seeks to describe the context of young children's gadget use. It also recognized the different concerns on children’s use and identify parents' mediation practices to address concerns. Samples of sixty parents with preschool children aged 3-5 years old living in an urban city were taken purposively for an in-depth interview to exhaust narration of their experiences. A descriptive research design was used, and results were coded to interpret the patterns and themes. The majority of parents allow access to gadgets daily with conditions. Mothers introduced gadgets even before 2 two years old. The mother has a significant influence on children’s use and choices of content. This also includes the media environment she cultivates at home, which promotes access. It started as a parent-directed activity and then developed into a child-directed activity. Gadgets are mainly used for entertainment and parenting tools. Despite the benefits, parents are concerned with its adverse effects. Parents are worried about health-related, behavioral, developmental, and sex-related concerns. However, parents still allow use despite the issues related to the use. The current benefits outweigh these concerns and risks. Parental mediation strategies are used to manage and mitigate its harmful effects on children's lives. Most parents use Restrictive mediation to enforce rules and discipline. More than half of them combine it with other strategies, such as technical and co-viewing. Active mediation is believed to be the most effective strategy to promote meaningful conversations over content and media consumption but is not commonly practiced.
In partial fulfillment for the Degree of Bachelor of Science in Family Life and Child Development
Thesis
Keywords: Young children; Gadgets; Screen media; Digital literacy; Parental mediation